Response to Fertilization Associated to Leaf Mineral Content in Strawberry - Agüero, Juan José (2015)
Leaf mineral content along the crop cycle may explain differences in response to fertilization among strawberry genotypes. A two year field experiment was conducted using responsive (‘Camarosa’, ‘Ventana’) and nonresponsive (‘Camino Real’, ‘Candonga’) to fertilization genotypes under proportional increases in nutrients supply: from a control dose “C” [120 kg nitrogen (N) ha−1, 70 kg phosphorus pentoxide (P2O5) ha−1, 220 kg potassium oxide (K2O) ha−1, 40 kg calcium oxide (CaO) ha−1 and 20 kg magnesium oxide (MgO) ha−1] to “1.33C” and “1.66C” in 2007 and to “1.5C” and “2C” in 2008. Response to fertilization was high (45–120%) at begining of harvesting and low (10-28%) at middle and end of harvesting. Correlation between leaf area and total yields was high (r ≈ 0.73) at begining of harvesting, except on ‘Camino Real’ (late and compact genotype). At begining of flowering and harvesting, responsive genotypes showed higher potassium (K) and lower calcium (Ca) leaf contents than nonresponsive genotypes, accentuated with the fertilization increase.